PENINGKATAN LITERASI DIGITAL DAN KREATIVITAS SISWA DALAM PEMBELAJARAN PAI MENGGUNAKAN MEDIA CHROMEBOOK BERBASIS APLIKASI CANVA - Maryam, Qorrie Aina; Arief, Armai; Ghofur, Abdul (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study aims to analyze the effectiveness of using Chromebooks with the Canva application to improve students' digital literacy and creativity in Islamic Religious Education (IRE) at the elementary school level. The integration of technology in IRE is an urgent need in the digital age that must be addressed. This study uses a mixed methods approach with an explanatory sequential strategy. The research subjects were fifth and sixth grade students. Data collection was conducted through tests, observations, interviews, and documentation, analyzed using Wilcoxon and N-Gain statistical tests, as well as qualitative descriptive analysis. The results showed: 1) There was a significant increase in the variables of digital literacy and creativity in both classes (Asymp. Sig < 0.001); 2) The effectiveness of the improvement in Grade V was classified as High (N-Gain Literacy 0.81; Creativity 0.85) and was superior to Grade VI (Medium category), challenging the assumption of linearity in cognitive development; 3) The scaffolding strategy was proven to be successful in transforming technical anxiety into computer self-efficacy; 4) The use of technology also strengthened the ethical dimension through the practice of validating sources of arguments. This study concludes that Chromebook and Canva are effective adaptive learning media for accelerating students' digital competence and creative character in Islamic Religious Education (IRE) subjects. ABSTRAK Penelitian ini bertujuan menganalisis efektivitas penggunaan media Chromebook berbasis aplikasi Canva dalam meningkatkan literasi digital dan kreativitas siswa pada mata pelajaran Pendidikan Agama Islam (PAI) di tingkat sekolah dasar. Integrasi teknologi dalam PAI merupakan urgensi di era digital yang perlu diatasi. Penelitian ini menggunakan metode kombinasi (mixed methods) dengan strategi explanatory sequential. Subjek penelitian adalah siswa Kelas V dan VI. Pengumpulan data dilakukan melalui tes, observasi, wawancara, dan dokumentasi, dianalisis menggunakan uji statistik Wilcoxon dan N-Gain, serta analisis deskriptif kualitatif. Hasil penelitian menunjukkan: 1) Terdapat peningkatan signifikan pada variabel literasi digital dan kreativitas di kedua kelas (Asymp. Sig < 0,001); 2) Efektivitas peningkatan pada Kelas V tergolong kategori Tinggi (N-Gain Literasi 0,81; Kreativitas 0,85) dan lebih unggul dibandingkan Kelas VI (kategori Sedang), menantang asumsi linieritas perkembangan kognitif; 3) Strategi scaffolding terbukti berhasil mengubah kecemasan teknis menjadi computer self-efficacy; 4) Pemanfaatan teknologi juga memperkuat dimensi etika melalui praktik validasi sumber dalil. Penelitian ini menyimpulkan bahwa Chromebook dan Canva adalah media pembelajaran adaptif yang efektif untuk mengakselerasi kompetensi digital dan karakter kreatif siswa pada mata pelajaran Pendidikan Agama Islam (PAI).